PELATIHAN PEMBUATAN MEDIA PEMBELAJARAN BAGI GURU-GURU SD NEGERI 3 TEGALLINGGAH - Ida Bagus Ardhi Putra (Politeknik Negeri Sriwijaya, 2022)
The education sector is one of the activity sectors affected by the rapid spread of the Covid-19 outbreak, so all learning activities are carried out online. The sudden change in learning causes many teachers to be unprepared for fully online learning. One of the schools experiencing this problem is SDN 3 Tegallinggah. The problem is that the teaching materials used by teachers for online learning are less attractive to students due to the lack of knowledge and skills of teachers in making learning media. For this reason, the ITEKES Bali community service team carried out training activities for making learning media for teachers at SDN 3 Tegallinggah. This activity is carried out for one day face to face. The training materials include making interesting learning media with Microsoft Powerpoint. The results of this PkM show that there is an increase in knowledge and skills in using powerpoint applications. Increased knowledge is evidenced by the pretest and posttest scores. The improvement of teacher skills is proven by the teachers being able to practice making presentation slides using powerpoint properly using the rules given during the training.